The Relevance of Pancasila in the Digital Age Amid Shifting Political Orientations among Indonesian Youth - Noorochmat Isdaryanto; Iwan Hardi Saputro; Eta Yuni Lestari (Universitas Negeri Semarang, 2025)
The rapid expansion of digital technology has transformed political communication, civic engagement, and value formation among young people, creating new challenges for maintaining the relevance of Pancasila in Indonesia’s democratic life. This study aims to examine the relevance of Pancasila amid shifting political orientations among Indonesian youth in the digital age and to explore its role as a normative framework for digital citizenship. Employing a qualitative descriptive approach through a systematic literature review, the study synthesizes findings from contemporary scholarly publications on digital politics, youth political participation, civic education, and political identity. The analysis reveals that digital media simultaneously expands opportunities for political participation while intensifying political polarization, misinformation, identity politics, and ideological fragmentation that may weaken the internalization of Pancasila values. The study further demonstrates that Pancasila remains a relevant civic ideology capable of fostering democratic ethics, social cohesion, and responsible political participation when integrated into digital literacy and civic education initiatives. The novelty of this study lies in positioning Pancasila not only as a constitutional ideology but also as an ethical framework for strengthening digital citizenship among Indonesian youth. These findings provide strategic insights for policymakers, educators, and civil society organizations in promoting democratic resilience and national identity within an increasingly digital political environment.